2015
DOI: 10.1016/j.tsf.2015.10.025
|View full text |Cite
|
Sign up to set email alerts
|

Structural and electrical characterizations of crack-free BaSi2 thin films fabricated by thermal evaporation

Abstract: The BaSi 2 semiconductor is a promising candidate for an earth-abundant solar cell absorber. In this study, we have realized a crack-free BaSi 2 film by a simple thermal evaporation technique on a CaF 2 substrate at a growth temperature of 500 • C for electrical characterization. A Si layer preliminarily formed on the substrate by sputtering is a key to obtain stoichiometric BaSi 2 film. Detailed structural characterization of the evaporated films with different Si layer thicknesses by X-ray diffraction, scann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 27 publications
2
29
0
Order By: Relevance
“…In order to find the φ i potential, the elliptical coordinates η, ψ defined by the relations (8) were used:…”
Section: Of 17mentioning
confidence: 99%
See 1 more Smart Citation
“…In order to find the φ i potential, the elliptical coordinates η, ψ defined by the relations (8) were used:…”
Section: Of 17mentioning
confidence: 99%
“…The resistance of thin layers is also affected by the anisotropic properties of the substrate [7]. The impact of defects on the electrical properties of films has been discussed by [8][9][10][11][12][13][14][15]. Physical vacuum deposition is used primarily when a high deposition index is required for a high-quality thin layer.…”
Section: Introductionmentioning
confidence: 99%
“…Si atoms to compensate excess Ba can originate from deposited Si thin films on various substrates. Hara et al have shown that pre-deposited amorphous Si (a-Si) is the key to obtaining stoichiometric BaSi2 thin films, and they succeeded in obtaining crack-free BaSi2 thin films on CaF2 substrates [39], which have a similar linear expansion coefficient to BaSi2 [40]. Other substrates, such as stainless steel, titanium [41], and Ge [42], have been used successfully as substrates for BaSi2 thin films.…”
Section: Vacuum Evaporationmentioning
confidence: 99%
“…Intrinsically doped BaSi2 shows n-type conductivity regardless of thin-film growth method. An electron concentration n varies from n ~ 10 16 cm -3 for MBE-grown BaSi2 films [16,50] to n >10 18 cm -3 for sputtered or vacuum-evaporated BaSi2 films [48,51,52]. A first-principles DFT supercell approach revealed that this n-type conductivity arises from Si vacancies [53].…”
Section: Intrinsically Doped N-basi2mentioning
confidence: 99%
“…We are therefore developing a thermal evaporation technique for BaSi 2 . So far, we have realized BaSi 2 films on various substrates such as silicon, 20 glass, 5 and CaF 2 , 21 and have revealed the BaSi 2 formation mechanism. 5,20,22,23 The composition of the vapor produced from BaSi 2 by thermal evaporation is Ba-rich in the initial stage and it changes to Si-rich as evaporation proceeds.…”
Section: Introductionmentioning
confidence: 99%